Avaliação de programas de retroanálise de bacias deflectométricas: aplicação a um trecho de uma rodovia federal - Lopes, Rosilene Alves (2019)
Brazil uses predominantly road freight transport, and in large part, its road network presents unsatisfactory conditions. The new design method, MeDiNa, was developed to help change this reality. The objective of this study was to evaluate backcalculation programs using a database of deflectometric basins measured with FWD deflectometer to try to identify how much the reinforcement design of the structures can be affected by the results obtained from each method. It was verified with the moduli obtained by the backcalculation if the reinforcement thicknesses indicated by the standards PRO 11/79 and PRO 269/94, from DNIT, provide the useful life of 10 years. Three backcalculation programs were used: PITRA-BACK, ELMOD and BackMeDiNa, which is a MeDiNa module. The analysis was done by applying the three methods to the actual data of segment surveys of a federal highway. It was concluded that the BackMeDiNa and ELMOD, when well calibrated, provide approximate moduli, but that the magnitude of the difference of the calculated moduli was not reflected in the life of the reinforcement. The DNIT reinforcement method provided a useful life of less than 10 years in all cases of the present study. The results indicate the importance of considering the elastic characteristics of pavement materials in the state of stresses and deformations resulting from the boundary conditions.